2021
DOI: 10.1371/journal.pone.0255428
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of students’ emotional intelligence, learning outcomes, and academic efficacy: A correlational study in higher education

Abstract: The purpose of this empirical study is to investigate the effects of Emotional Intelligence (EI) on learning outcomes (social, cognitive, self-growth outcomes and satisfaction with the university experience) of students in Chinese research universities. This study further examines the mediating role of student trust in teachers (emotional and cognitive learning) and learning orientation (commitment to learning) in the relationship between EI and learning outcomes. This intent of this study was to examine the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 84 publications
(151 reference statements)
1
30
0
Order By: Relevance
“… Han et al (2017) showed that abusive supervision had an indirect negative relationship with employee creativity via its impact on emotional exhaustion. Emotions play a vital part in success and failure of personnel in routine assignments ( Shafait et al, 2021c , d ). Akram et al (2019) found that abused employees usually suffer from emotional exhaustion and tend to promote counterproductive work behaviors.…”
Section: Introductionmentioning
confidence: 99%
“… Han et al (2017) showed that abusive supervision had an indirect negative relationship with employee creativity via its impact on emotional exhaustion. Emotions play a vital part in success and failure of personnel in routine assignments ( Shafait et al, 2021c , d ). Akram et al (2019) found that abused employees usually suffer from emotional exhaustion and tend to promote counterproductive work behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the higher education sector in the COVID-19 era focuses on blended learning mode classes and creates psychological issues owing to unpredictable situations. Therefore, it was important to explore emotional intelligence, cognitive engagement, and study habits in these circumstances [ 18 ]. Third, few studies have explored the direct connections between EI and study habits.…”
Section: Introductionmentioning
confidence: 99%
“…Higher education institutions teach and advocate consistent change and learning ( Shafait et al, 2021b ). Learning outcomes (social, cognitive, self-growth outcomes, and satisfaction with university experience) of HEIs personnel, therefore, are considered vital in their respective domain ( Shafait et al, 2021c ).…”
Section: Introductionmentioning
confidence: 99%